2017
DOI: 10.1017/asb.2017.21
|View full text |Cite
|
Sign up to set email alerts
|

Parsimonious Parameterization of Age-Period-Cohort Models by Bayesian Shrinkage

Abstract: Age-period-cohort models used in life and general insurance can be over-parameterized, and actuaries have used several methods to avoid this, such as cubic splines. Regularization is a statistical approach for avoiding over-parameterization, and it can reduce estimation and predictive variances compared to MLE. In Markov Chain Monte Carlo (MCMC) estimation, regularization is accomplished by the use of mean-zero priors, and the degree of parsimony can be optimized by numerically efficient out-of-sample cross-va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…We follow Venter and Şahin (2017) in assuming there is no overall trend across the cohorts. This can be forced by fitting a linear trend to the cohort parameters r j−i and subtracting it from the parameters.…”
Section: Methodology For Opioid Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…We follow Venter and Şahin (2017) in assuming there is no overall trend across the cohorts. This can be forced by fitting a linear trend to the cohort parameters r j−i and subtracting it from the parameters.…”
Section: Methodology For Opioid Applicationmentioning
confidence: 99%
“…The dummies specify how many times a given slope change is summed in the calculation of the level parameter for a data point. Venter and Şahin (2017) use a similar approach. A related paper is Gao and Meng (2017), who use Bayesian regularization for cubic spline fitting of an age-cohort model.…”
Section: Introductionmentioning
confidence: 99%
“…Actually Hunt and Blake (2014) allow the possibility of different trends with different age weights either simultaneously or in succession. Venter and Şahin (2018) suggest an informal test for the need for multiple trends, and find that they indeed help in modeling the US male population for ages 30-89. In the example here we fit the model to ages 50 and up, and did this test, which suggested that one trend is sufficient, so the model is presented in that form.…”
Section: Joint Mortality Modeling By Shrinkagementioning
confidence: 99%
“…Selecting the scale parameter of the Laplace or Cauchy prior for MCMC, or the λ shrinkage parameter for lasso or ridge regression, requires a balancing of parsimony and goodness of fit. Taking the parameter that optimizes elpd loo is one way to proceed, and that was the approach taken in G. Venter and Şahin (2017). However this is not totally compatible with the posterior mean philosophy, as it is a combination of Bayesian and predictive optimization.…”
Section: C Selecting the Degree Of Shrinkagementioning
confidence: 99%
“…G. G. Venter, Gutkovich, and Gao (2017) model loss triangles with row, column, and diagonal parameters in slope change form fit by random effects and lasso. G. Venter and Şahin (2017) use Bayesian shrinkage priors for the same purpose in a mortality model that is similar to reserve models. G. Gao and Meng (2017) use shrinkage priors on cubic spline models of loss development.…”
Section: Introductionmentioning
confidence: 99%